Pengaruh Tumpangsari dengan Tanaman Rimpang Terhadap Infeksi Awal Ganoderma boninense pada Bibit Kelapa Sawit (Elaeis guineensis) - Rudi Putra Munandar; Suwandi Suwandi; Suparman Suparman (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2021)
Basal stem rot (BSR)Â  caused by white decay fungus, Ganoderma boninense is known to cause significant losses in oil palm plantation in Southeast Asia. This study determined the effect of oil palm mixed planting with rhizomatous plants, galangal (Alpinia galangal), Java curcumin (Curcuma longa), or ginger (Zingiber officinale) on initial infection of BSR. Plants were inoculated by attachment of rubber wood block colonized with G. boninense to the main roots. Infection was measured as length of root necrosis and confirmed by culturing on Ganoderma selective medium. Infection was also assessed by total activity of ligninase as measured by RBBR decolorization. The results showed that G. boninense infection at 1-month-post inoculation was lower on mixed planting with all rhizomatous plants, and the suppression of infection was still occured in mixed planting with galangal. Total activity of ligninase on oil palm roots was delayed on mixed planting compared to that of higher activity on single planting at 1-month-post inoculation. This result highlights benefit of mixed planting of oil palm withÂ  rhizomatous plants in delaying initial infection of BSR patogen.